Hubungan Tingkat Kesulitan Belajar Dengan Hasil Mata Kuliah Anatomi Mahasiswa Kebidanan Tingkat I Stikes Panrita Husada Bulukumba Tahun 2016 - Husnul Khatimah; Ainun Musvira; Selpi.U Selpi (JMNS, 2021)
Learning difficulties are not always caused by factor of intelligence, but also because of non-intelligence factors. IQ (Intellectual Quality) is high does not necessarily guarantee success in learning. Factors learning difficulties can come from within the students themselves as less motivated, less effective study habits and skills to follow the lessons less. The purpose of this research is to find the relationship between the dependent and independent variables namely Relations Difficulty Study Results Subjects Anatomy Student Midwife Academy Level 1 STIKes Panrita Husada Bulukumba. This type of research is a Cross Sectional Study. This study was conducted in May 2016. The population as defined in this study were all students of midwifery DIII level 1 STIKes Panrita Husada Bulukumba who are following the lesson as many as 110 students. The sample in this research is partly DIII midwifery students at level 1 STIKes Panrita Husada Bulukumba totaling 52 students with sampling technique Random Sampling. The results showed that of the respondents who have learning difficulties as many as 21 people (40.4%) and who do not have learning difficulties as many as 31 people (59.6%). The results showed that the number of respondents who have a good learning outcomes as many as 33 people (63.5%) and education outcomes are lacking many as 19 people (36.5%). There is a relationship with the level of difficulty of learning outcomes anatomy courses students midwifery academy level 1 STIKes Panrita Husada Bulukumba. Can promote the development of science to increase knowledge about the difficulty of learning the results of anatomy courses.